Islamic Digital Storytelling in Enhancing Students’ Recount Text Writing Skills and Learning Motivation: A Systematic Literature Review - Rahmayuni, Sisri; Nora, Wiwit Engrina; Syafitri, Widya; Sesmiarni, Zulfanny (El-Rusyd, 2025)
This study aims to examine the use of Islamic digital storytelling media in improving students’ recount text writing skills and learning motivation through a systematic literature review. The rapid development of educational technology has encouraged teachers to integrate digital media into English language teaching, particularly in writing instruction. Digital storytelling has emerged as a promising approach that combines narrative, multimedia elements, and student-centered learning, while Islamic values embedded in learning media contribute to character education. This study employed a qualitative systematic literature review method by analyzing open-access articles from national and international journals indexed in Sinta, Scopus, and other reputable databases published within the last five years. The data were collected through documentation techniques and analyzed using content analysis procedures, including identifying themes, categorizing findings, and synthesizing patterns across studies. The findings indicate that Islamic digital storytelling significantly enhances students’ writing performance in recount texts, particularly in organization of ideas, language use, and creativity. Additionally, it positively influences students’ learning motivation, engagement, and confidence. The integration of Islamic values also strengthens students’ moral awareness and learning attitudes. This study implies that Islamic digital storytelling can serve as an effective alternative learning medium that supports both cognitive and affective domains in English language learning at the secondary school level.